Respuesta :

Simplifying
a + 4b = 5b + -3a

Reorder the terms:
a + 4b = -3a + 5b

Solving
a + 4b = -3a + 5b

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '3a' to each side of the equation.
a + 3a + 4b = -3a + 3a + 5b

Combine like terms: a + 3a = 4a
4a + 4b = -3a + 3a + 5b

Combine like terms: -3a + 3a = 0
4a + 4b = 0 + 5b
4a + 4b = 5b

Add '-4b' to each side of the equation.
4a + 4b + -4b = 5b + -4b

Combine like terms: 4b + -4b = 0
4a + 0 = 5b + -4b
4a = 5b + -4b

Combine like terms: 5b + -4b = 1b
4a = 1b

Divide each side by '4'.
a = 0.25b

Simplifying
a = 0.25b